A reconfiguration of the sex trade: How social and structural changes in eastern Zimbabwe left women involved in sex work and transactional sex more vulnerable. - Jocelyn Elmes; Morten Skovdal; Kundai Nhongo; Helen Ward; Catherine Campbell; Timothy B Hallett; Constance Nyamukapa; Peter J White; Simon Gregson (PLoS ONE)
Understanding the dynamic nature of sex work is important for explaining the course of HIV epidemics. While health and development interventions targeting sex workers may alter the dynamics of the sex trade in particular localities, little has been done to explore how large-scale social and structural changes, such as economic recessions-outside of the bounds of organizational intervention-may reconfigure social norms and attitudes with regards to sex work. Zimbabwe's economic collapse in 2009, following a period (2000-2009) of economic decline, within a declining HIV epidemic, provides a unique opportunity to study community perceptions of the impact of socio-economic upheaval on the sex trade. We conducted focus group discussions with 122 community members in rural eastern Zimbabwe in January-February 2009. Groups were homogeneous by gender and occupation and included female sex workers, married women, and men who frequented bars. The focus groups elicited discussion around changes (comparing contemporaneous circumstances in 2009 to their memories of circumstances in 2000) in the demand for, and supply of, paid sex, and how sex workers and clients adapted to these changes, and with what implications for their health and well-being. Transcripts were thematically analyzed. The analysis revealed how changing economic conditions, combined with an increased awareness and fear of HIV-changing norms and local attitudes toward sex work-had altered the demand for commercial sex. In response, sex work dispersed from the bars into the wider community, requiring female sex workers to employ different tactics to attract clients. Hyperinflation meant that sex workers had to accept new forms of payment, including sex-on-credit and commodities. Further impacting the demand for commercial sex work was a poverty-driven increase in transactional sex. The economic upheaval in Zimbabwe effectively reorganized the market for sex by reducing previously dominant forms of commercial sex, while simultaneously providing new opportunities for women to exchange sex in less formal and more risky transactions. Efforts to measure and respond to the contribution of sex work to HIV transmission need to guard against unduly static definitions and consider the changing socioeconomic context and how this can cause shifts in behavior.